Heads of the Operational Department of the Armavir-Tuapse Railway (a personal factor in the History) - G. N. Bychkov (Вестник Майкопского государственного технологического университета, 2025)
Relevance. The issues considered in the article are a poorly studied aspect of the operational period of the history of the Armavir-Tuapse Railway Joint-Stock Company. Researchers and local historians studying the development of railway communication in the North Caucasus at the beginning of the 20th century did not focus on the people who managed one of the most important regional highways that connected the Black Sea coast with the all-Russian railway network. This, in turn, does not allow us to comprehensively evaluate and analyze the events of the past and clearly demonstrates the relevance of this research.The goal of the research is to reconstruct the events associated with changes in the management of the operational department of the Armavir-Tuapse Railway from 1914 to 1920, and to restore the professional biographies of the engineers who headed it. This chronological framework is determined by the establishment of the position of the road manager in 1914 and the nationalization of the transport enterprise in 1920, which entailed its liquidation as a legal entity due to the transformation of the general state structure of Russia.The principles of historicism and objectivity have become the methodological basis of the research. The approaches of systematization and generalization, as well as problem-chronological and retrospective methods have been used. Unpublished documents stored in the federal, regional and municipal archives of the Russian Federation have been chosed as a source base for the research.The result of the research. Apart from introducing professional biographies of railway engineers and the chronology of changes in the management of the operational management of the Armavir-Tuapse railway, the role and characteristics of the personal contribution to the organization of railway freight and passenger transportation on this highway have been analyzed.